2022
DOI: 10.1002/ctm2.992
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐192‐5p/RB1/NF‐κBp65 signaling axis promotes IL‐10 secretion during gastric cancer EMT to induce Treg cell differentiation in the tumour microenvironment

Abstract: Background Regulatory T (Treg) cells are important components of the tumour microenvironment (TME) that play roles in gastric cancer (GC) metastasis. Although tumour cells that undergo epithelial‐mesenchymal transition (EMT) regulate Treg cell function, their regulatory mechanism in GC remains unclear. Methods The miR‐192‐5p was identified by examining three Gene Expression Omnibus GC miRNA expression datasets. RNA immunoprecipitation (RIP) and dual‐luciferase reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Previous studies reported that miR192 regulated the EMT pathway ( Khella et al, 2013 ). Song et al confirmed that miR‐192 promoted EMT of gastric cancer, migration and invasion by targeting RB1 ( Song et al, 2022 ). In additional, the previous study has demonstrated that miR-192 was significantly upregulated in cisplatin-resistant lung cancer cells, and miR-192 induced cisplatin resistance through activating the NF-κB pathway ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported that miR192 regulated the EMT pathway ( Khella et al, 2013 ). Song et al confirmed that miR‐192 promoted EMT of gastric cancer, migration and invasion by targeting RB1 ( Song et al, 2022 ). In additional, the previous study has demonstrated that miR-192 was significantly upregulated in cisplatin-resistant lung cancer cells, and miR-192 induced cisplatin resistance through activating the NF-κB pathway ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 98%
“…In a cohort of 106 burn patients (who are prone to burn sepsis), increased levels of IL-10 expressed by Tregs are related to poorer clinical outcomes and prognosis [31]. Meanwhile, IL-10 can promote the differentiation of Tregs [32]. Apoptosis and pyroptosis of immune cells are master factors in the development of lymphopenia.…”
Section: Tregs Release Immunosuppressive Cytokines To Regulate Immuno...mentioning
confidence: 99%
“…They are widely present in body fluids such as plasma, serum, and tumor patients’ exocytosis. Moreover, increasing studies have shown that circulating ncRNAs in the blood of tumor patients can be detected in large quantities and used as biomarkers for GC [ 169 , 170 ]. Our previous studies have shown that circPTPN22, which is up-regulated in GC plasma, can effectively differentiate GC patients from healthy controls; its AUC value can reach 0.857.…”
Section: Clinical Application Of Liquid Biopsy Biomarkers In Gcmentioning
confidence: 99%